2014
DOI: 10.4236/me.2014.58081
|View full text |Cite
|
Sign up to set email alerts
|

Household Savings and Productive Capital Formation in Rural Vietnam: Insurance vs. Social Network

Abstract: In this paper, we investigate the role of the social network nexus and the insurance nexus in determining household savings and productive capital formation in rural Vietnam. We analyze the issue in two dimensions, stocks and flows, and consider the exposure to negative shocks. The instrumental variable method is employed and unlike previous studies, we account for the endogeneity of all concerned variables. The results indicate that the social network nexus has more impacts in "ex ante" rather than in "ex pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…This holds true for the whole sample as well as for urban and rural households. Our results are consistent with the findings of Gries and Dung (2014) for rural Vietnam.…”
Section: Empirical Findings and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This holds true for the whole sample as well as for urban and rural households. Our results are consistent with the findings of Gries and Dung (2014) for rural Vietnam.…”
Section: Empirical Findings and Discussionsupporting
confidence: 93%
“…The gender of the household head is known to be a very common factor affecting household saving behaviour (Abdelkhalek et al, 2010;Gries and Dung, 2014;Minh et al, 2013;Schunk, 2009). In many papers it is found that the saving behaviours of males and females are not homogeneous.…”
Section: Gender Of Household Head (Male/female)mentioning
confidence: 99%
“…From the micro perspective, savings is an important factor of household welfare, understanding the social-economic determinants that prompt households to save is therefore a worthwhile topic of academics and policymakers. Some empirical studies attempt to identify the key influences driving the saving behavior of households in Vietnam, including demographics (Nguyen, Nguyen, Trinh, Phung, & Le, 2013), social capital (Newman, Tarp, & Van Den Broeck, 2014), and social networks and insurance (Gries & Van Dung, 2014). Recently, the growing literature on social status and economic growth has provided several explanations for how and why income inequality can impact on households' savings.…”
Section: Introductionmentioning
confidence: 99%